Increased Noradrenaline Levels in the Rostral Pons can be Reversed by M1 Antagonist in a Rat Model of Post-traumatic Stress Disorder - AYDIN OMAY, BANU; CABADAK, HÜLYA; GÖREN, MEHMET ZAFER (SPRINGER/PLENUM PUBLISHERS, 2013)
The dysregulation of hypothalamic-pituitary-adrenal axis and noradrenergic, serotonergic and glutamatergic systems are thought to be involved in the pathophysiology of post-traumatic stress disorder. The effect of selective M1 muscarinic receptor antagonist, pirenzepine on anxiety indices was investigated by using elevated plus maze, following exposure to trauma reminder. Upon receiving the approval of ethics committee, Sprague-Dawley rats were exposed to dirty cat litter (trauma) for 10 min and 1 week later, the rats confronted to a trauma reminder (clean litter). The rats also received intraperitoneal pirenzepine (1 or 2 mg/kg/day) or saline for 8 days. Noradrenaline (NA) concentration in the rostral pons was analyzed by HPLC with electrochemical detection. The anxiety indices of the rats subjected to the trauma reminder were increased when compared to control rats (p < 0.05). Pirenzepine treatment in traumatized rats displayed similar anxiety indices of non-traumatized rats treated with physiological saline. Although freezing time was prolonged with pirenzepine in traumatized groups the change was not found statistically significant. The NA level was 1.5 +/- A 0.1 pg/mg in non-traumatized rats and increased to 2.4 +/- A 0.2 pg/mg in traumatized rats. Bonferroni post hoc test revealed that the NA content of the rostral pons of the traumatized rats treated with physiological saline was significantly higher than the content of other groups (p < 0.01). We conclude that NA content in the rostral pons increases in respect to confrontation to a trauma reminder which can be reversed by M1 antagonist pirenzepine indicating the roles of M1 receptors.
Keywords: Pirenzepine; Elevated plus maze; Muscarinic; Locus ceruleus; Anxiety; HPLC; MUSCARINIC ACETYLCHOLINE-RECEPTORS; CORTICOTROPIN-RELEASING-FACTOR; PITUITARY-ADRENOCORTICAL AXIS; LOCUS-COERULEUS; ANIMAL-MODEL; BEHAVIORAL DEPRESSION; BRAIN-STEM; NOREPINEPHRINE; NUCLEUS; ANXIETY